2011
DOI: 10.1128/jvi.05373-11
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the Envelope Proteins in the Amplification of Covalently Closed Circular DNA and Completion of Synthesis of the Plus-Strand DNA in Hepatitis B Virus

Abstract: Covalently closed circular DNA (cccDNA), the nuclear form of hepatitis B virus (HBV), is synthesized by repair of the relaxed circular (RC) DNA genome. Initially, cccDNA is derived from RC DNA from the infecting virion, but additional copies of cccDNA are derived from newly synthesized RC DNA molecules in a process termed intracellular amplification. It has been shown that the large viral envelope protein limits the intracellular amplification of cccDNA for duck hepatitis B virus. The role of the envelope prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
67
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 57 publications
1
67
0
Order By: Relevance
“…To analyze the potential effects of the HBc mutants on reverse transcription and CCC DNA synthesis inside the cells, we transfected HepG2 and Huh7 cells with HBV-replicating constructs harboring these NTD mutations. Two versions of these constructs were used, either with or without the expression of the viral envelope proteins, which are known to regulate CCC DNA formation (9,27,29). We found that in both cell lines, either with or without expression of the envelope proteins, the L95A and K96A mutants showed a core DNA (i.e., NC-associated DNA) pattern similar to that of the WT ( Fig.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…To analyze the potential effects of the HBc mutants on reverse transcription and CCC DNA synthesis inside the cells, we transfected HepG2 and Huh7 cells with HBV-replicating constructs harboring these NTD mutations. Two versions of these constructs were used, either with or without the expression of the viral envelope proteins, which are known to regulate CCC DNA formation (9,27,29). We found that in both cell lines, either with or without expression of the envelope proteins, the L95A and K96A mutants showed a core DNA (i.e., NC-associated DNA) pattern similar to that of the WT ( Fig.…”
Section: Resultsmentioning
confidence: 78%
“…The two alternative fates of mature NCs (i.e., envelopment versus CCC DNA amplification) are known to be regulated by the viral envelope proteins (9,(27)(28)(29). Since HBc forms the NC shell, it is also likely to play a key role in these processes (30,31).…”
mentioning
confidence: 99%
“…Similarly, ablation of HBsAg also increased intranuclear HBV cccDNA formation, although to a lesser extent (7). Detailed examination using large (L), middle (M), and small (S) envelope protein mutant constructs suggested that L and M proteins were mainly responsible for this phenomenon (28). In liver tissues from CHB patients, intrahepatic HBsAg levels showed an inverse correlation with serum HBsAg titers (29).…”
Section: Localization Of Hbcag In Clinical Hbv Infectionmentioning
confidence: 93%
“…Regarding viral factors, the envelope proteins, especially the largest one, L, negatively regulate CCC DNA formation (10,(12)(13)(14)(15). In addition, as NC uncoating and RC DNA release must precede CCC DNA formation, the maturation-associated NC destabilization, which we have reported recently (16), is likely a prerequisite for CCC DNA formation.…”
mentioning
confidence: 99%